Reflections on the Pitti Friendship Portrait of Rubens: In Praise of Lipsius and in Remembrance of Erasmus - Zurawski, Simone (The sixteenth century journal, 1992)
This study directs attention away from the prevailing Neostoic readings of the so-called Four Philosophers of Rubens, and demonstrates instead that the imagery reflects aspects of an apologetic movement which flourished in the circle of Lipsius' former pupils soon after his death. It is well known that Lipsius was one of the most controversial men of the age. Brought to the foreground here is the character of his posthumous defense, led by Balthasar Moretus and Philip Rubens. Peter Paul Rubens became involved in the stir of events by designing plates for a new edition of Lipsius' Opera Omnia, and by painting a memorial portrait of Lipsius for Moretus. The group portrait now in the Pitti is the most complex yet subtle of Rubens' several contributions and is an enduring monument of that trend overall. The artist here assumes the epideictic tone found in certain verses written by the Lipsian "alumni" that express bonds of familial affection in the comfort of Lipsius' idealized library. These sentiments throw into the background the agendas with which Lipsius had been connected, including Neostoicism. The composition would have evoked parallelism to certain famous portraits of Erasmus, who like Lipsius, was caught in the midst of great conflict yet elicited love and adoration from his pupils. This parallelism was well in effect in Lipsian circles, since a number among them were working to revive Erasmus' reputation at the same time they were composing their defenses of Lipsius. This clannish movement which came to the defense of Lipsius inspired the painting of the Pitti Friendship Portrait.